Inovasi Pendidikan Keahlian Sekolah Menengah Kejuruan Berbasis Pesantren di Kabupaten Banyuwangi - Kholilur Rahman (UIN Sunan Ampel Surabaya, 2018)
This paperwork analyzes innovation in education by High Vocational School (SMK) under pesantren institution in Banyuwangi Regency. Within the framework of cultural and micro poliotics of school theory, power (politics) is able to optimize innovation planning rather than it is within approaches of cultural, striuctural, or rationale of institutional leaders. Innovation in terms of quality of vocational education is highly supported by professional teachers and their experience beackground in education. Further, in terms of student outcomes and public relations with workplaces, leadership and interrelation of kiai’s power and pesantren become crusial factor enhancing edeucational innovation in vocational school under pesantren.